KONTRIBUSI KNOWLEDGE MANAGEMENT DALAM MENGEMBANGKAN DAN MEMPERTAHANKAN COMPANY'S COMPETITIVE ADVANTAGE DI ERA KNOWLEDGE ECONOMY - Bambang Wiharto; Amelia Setiawan (Universitas Trisakti, 2007)
Knowledge becomes a strong power to win competition in this knowledge economy era. Executives and managers who manage and direct the organization need information support and knowledge in developing company strategies and to perform a better decision making in order to sustain and build strong competitive advantage. How an organization manages their information and knowledge will become a critical success factor for being a market leader. Knowledge which contain of experience, intuition, best practices and lessons learned becomes intangible asset which could be used to reach company goals and objectives. The knowledge management systems one collect, process, store, retrieve, communicate and share data, information and knowledge it becomes a tool to create value for organization and its stakeholders and accelerate development of an appropriate culture to become a knowledge based organization. The piper is a literatur review that das cuss. Is knowledge the ultimate competitive advantage? How would a company put knowledge management into practice? Is Knowledge Management practices will yield the competitive advantage and sustaining it? These and related issues are the focus of this paper.Keywords : Knowledge, knowledge management, information